A Tier 3 Method for Enteric Methane in Dairy Cows Applied for Fecal N Digestibility in the Ammonia Inventory - Bannink, André; Spek, Wouter J.; Dijkstra, Jan; Šebek, Leon B. J. (Frontiers in Sustainable Food Systems, 2018)
Current inventory of N emission from cow excreta relies on faecal N digestibility data in Dutch feeding tables, assuming additivity of dietary ingredients to obtain diet values (CVB model). Alternatively, faecal N digestibility can be estimated by a dynamic, mechanistic model of digestion in the gastrointestinal tract, currently used as Tier 3 for enteric methane prediction in the Netherlands (Tier 3 model). Estimates of in situ rumen degradation characteristics for starch, NDF and protein used as an input for the Tier 3 model were based on Dutch feeding tables (the protein evaluation system). Both methods were evaluated on an independent dataset on faecal N digestibility that was constructed from peer-reviewed papers on N balance data for dairy cows published since 1999 (54 trials, 242 treatment means). Results indicate that observed apparent faecal N digestibility (67.0 ± 6.77 %) was systematically over-predicted in particular by the CVB model (73.8 ± 4.35 %) compared to the Tier 3 model (69.8 ± 4.52 %). For the dataset including only observations from Dutch trials the observed faecal N digestibility (70.4 ± 7.33 %) was also systematically over-predicted by the CVB model (76.4 ± 5.27 %) but not by the Tier 3 model (69.7 ± 5.81 %). Mixed model analysis with study as random factor indicated the slope of the regression between observed and predicted faecal N digestibility to be smaller than 1, in particular for the CVB model (CVB model slope varied between 0.405 and 0.560 and Tier 3 model slope between 0.418 and 0.657). The over-prediction by the CVB model with 6 to 7 %-units of digestibility will lead to an over-predicted ammoniacal N excretion (urinary N) in ammonia inventory, and biased estimation of N mitigating potential of nutritional measures. The present study demonstrates the benefit of using the Tier 3 model to predict the average level of apparent faecal N digestibility compared to the CVB model. The general estimates of in situ rumen degradation characteristics for starch, NDF and protein used as an input for the Tier 3 model seemed applicable for the Dutch trials but less so for the non-Dutch trials.